TEKNOLOGI PAKAN MANDIRI UNTUK PENGEMBANGAN IKAN SIDAT DI PEDESAAN - Purnama Sukardi; Taufiq Budi Pramono; Taufan Harisam; Sri Marnani; Tjahyo Winanto; Norman Arie Prayogo (Dinamika Journal : Pengabdian Masyarakat, 2021)
Dessimination of the development of eel fish farming in rural areas with the aimed to increase ability and competitiveness of self-help group through the independence of making pasta feed for eels. Adult teaching methods and the active participation of trainees were used in this dissemination. The results showed that the individual absorption of the material for the dissemination of feed-making technology was still low (<40%), however the absorption of group was high (80%). The material of Good Aquaculture Practise (GAP) can be mastered very well (80%), however export training materials are still low (<30%).